PRODUKTIVITAS PENGELUARAN DOLOK KAYU TUSAM DENGAN SISTEM KABEL LAYANG IWAFUJI 115 - Zakaria Basari (Pusat Penelitian dan Pengembangan Hasil Hutan, 2002)
This report deals with assessing the performance of tusam (Pinus merkusii Jungh et de Vries) log - removal using particular skyline system. The assessment in this regard is pointed out by the aim of this study, i.e. observing the productivity and operation cost of such removal.Related with those cases, investigation has been conducted and located in Cikajang Sub Forestry District, Garut Forest District, under the Indonesian State Forest Enterprise in West Java. The topographical location has a slope at about 5° - 50° with altitude ranging around 900 - 1000 m above sea level. The skyline machine used was a yarder manufactured in Japan with the brand name as